2009
DOI: 10.1017/s0032247409990131
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the harsh. Objective and subjective living conditions in Nunavut

Abstract: This paper simultaneously analyses some objective and subjective living conditions in Nunavut (federal territory of Canada located in the Arctic) in 2001: population, housing, language, education, economic activities, health, social problems and geographic mobility. It examines original descriptive statistics from the Survey of living conditions in the Arctic and other sources. In some cases the results confirm the ordinary depressing picture of Inuit conditions, but in other cases statistics qualify or even c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Equally, research has indicated that social networks through which traditional foods are shared between and within households are often weaker in RICs, a function of demographics, predominance of livelihoods based on the waged economy, in-migration and transiency in habitation [47-49]. Moreover, the larger settlements, while increasingly prosperous, have significant pockets of inequality, characterized by high and persistent unemployment, poverty, and house overcrowding [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…Equally, research has indicated that social networks through which traditional foods are shared between and within households are often weaker in RICs, a function of demographics, predominance of livelihoods based on the waged economy, in-migration and transiency in habitation [47-49]. Moreover, the larger settlements, while increasingly prosperous, have significant pockets of inequality, characterized by high and persistent unemployment, poverty, and house overcrowding [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…That is the case with the Survey of Living Conditions in the Arctic (SLiCA), entrenched into the 2001 and 2006 Aboriginal People Survey in Canada (Duhaime and Le´vesque 2014;É douard and Duhaime 2013;Kruse et al 2008;Morin et al 2010). However, for the purposes of the present study, the unique advantage of the Nunavik Inuit Health Survey (Lavoie et al 2007) is that it produces assessments of a population's health, which Sen considers a fundamental capability.…”
Section: Statistical Data Sourcesmentioning
confidence: 91%
“…Northern Canada refers to regions in near and above 50°N latitudes categorized into ASHRAE climate zones 7 and 8 41 (see Figure 1-a ). Climatic features drastically change by moving towards high latitudes and sub-Arctic regions of Canada [41][42][43] resulting in challenging living and working conditions 44,45 . Seasonal photoperiods and solar radiation, the most influential factors on the climate and human lives 18,26,46 , could change from a few hours of daylight in the winter to almost no-darkness during the summer in a high-latitude Canadian City such as Cambridge Bay, Nunavut, Canada [69.1°N] (Figure 1-b).…”
Section: Climatic Challenges In Northern Canadamentioning
confidence: 99%